The Effect of Recessions on Potential Output Estimates: Size, Timing, and Determinants - Jonas Dovern; Christopher Zuber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze when and how much OECD estimates of potential output are revised after recessions and which factors explain the size of these revisions. Inter alia, we find that following a recession, the OECD substantially revises downwards potential output, those revisions are larger than what is to be expected under the assumption of no hysteresis, and the recession depth, the primary balance, and the current account balance are predictors of post-recession revisions of potential output.
Keywords: E32; 330